Toxicogenomic analysis identifies the apoptotic pathway as the main cause of hepatotoxicity induced by tributyltin. (November 2016) - Zhou, Mi; Feng, Mei; Fu, Ling-ling; Ji, Lin-dan; Zhao, Jin-shun; Xu, Jin
Abstract: Tributyltin (TBT) is one of the most widely used organotin biocides, which has severe endocrine-disrupting effects on marine species and mammals. Given that TBT accumulates at higher levels in the liver than in any other organ, and it acts mainly as a hepatotoxic agent, it is important to clearly delineate the hepatotoxicity of TBT. However, most of the available studies on TBT have focused on observations at the cellular level, while studies at the level of genes and proteins are limited; therefore, the molecular mechanisms of TBT-induced hepatotoxicity remains largely unclear. In the present study, we applied a toxicogenomic approach to investigate the effects of TBT on gene expression in the human normal liver cell line HL7702. Gene expression profiling identified the apoptotic pathway as the major cause of hepatotoxicity induced by TBT. Flow cytometry assays confirmed that medium- and high-dose TBT treatments significantly increased the number of apoptotic cells, and more cells underwent late apoptosis in the high-dose TBT group. The genes encoding heat shock proteins (HSPs), kinases and tumor necrosis factor receptors mediated TBT-induced apoptosis. These findings revealed novel molecular mechanisms of TBT-induced hepatotoxicity, and the current microarray data may also provide clues for future studies. Highlights: Use toxicogenomic approach to investigate the hepatotoxicity of TBT. Gene expression profiling identified the apoptotic pathway as the major cause. Flow cytometry assays confirmed that TBT significantly induces apoptosis. Genes encoding HSPs, kinases and TNFRs mediated TBT-induced apoptosis Loss of the cytoprotective actions of HSPs was involved in TBT-induced toxicity.